The dispute between Latin and Castilian in Spain of the Golden Age - Zuili, Marc (Studia Europaea Gnesnensia, 2012)
This article analyses the antagonism which made itself evident in the usage of Latin and Castilian, also referred to as the language of the romance, in the era of the Spanish Habsburgs. For this purpose, it was necessary to draw upon a body of 16th and 17th century texts, in particular such authors as Juan de Valdés, Pedro Mexía, Luis de León, Martín de Viciana, Bernardino Montaña de Monserrate or Pedro Jiménez de Prexano. In his analysis, the author relied on three voluminous anthologies: 1929 “Las apologías de la lengua castellana en el siglo de oro” by José Francisco Pastor, “Antología de elogios de la lengua española” published by Germán Bleiberg in 1951 and the most up-to-date, 2006 “Antología en defensa de la lengua y literatura españolas” (siglos xvi y xvii) by Encarnación García Dini. Author’s particular attention was drawn to the fact that in the analysed texts those which praise Castilian prevail, at the expense of Latin. While under Charles V the defence of the Castilian tongue was vigorous and powerful, during the reign of Philip II it is more discreet, and since the beginning of the 17th century it becomes a genuine priority for the Spanish authors. This is borne out by the amount of praise of Latin at the time. In the course of the narration the author focused on a threefold task: to present some of the apologies of Castilian, to present and analyse the arguments used in its defence by selected authors and to investigate the causes behind the subsidence of the tendency as time progressed.